Effectiveness of NDT method in cases of Cerebral Palsy Ataxia - zahra, nabilla frizky; putri, aulia kurnianning; rahmawati, rizka asna (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2024)
Background: As many as 2.5% of children out of 1000 live births in the world have a higher risk of developing CP, and as many as 70% of CP occurs if the baby's birth weight is low, infections during pregnancy and the child's growth and development, obstruction of the birth canal, and stress experienced by the mother. causes the baby to experience CP. Objective: The case study aims to determine the benefits of the NDT approach method for CP Ataxia in improving movement control, eliciting reflexes, increasing core stability and lower extremity muscle strength, and increasing functional activity. Method: In the case of CP Ataxia, the NDT method is used in the form of handling with falling reflex training, handling with training standing on a balance board, facilitation with training getting up and down a balance board, facilitation with walking and pushing a chair. Evaluation was carried out 4 times over 3 weeks with GMFM, and checking balance reflexes. Results: After physiotherapy, it was found that there was an increase in movement control, the emergence of reflexes in children where the appearance of the protective side ward reflex increased starting at T3, while the emergence of the paracute side ward reflex began at T4. There was an increase in muscle strength and functional activity measured by GMFM, resulting in T1 63.36%; T2 63.36%; T3 64.36%; T4 67.3%. Conclusion: The NDT approach as a method for managing CP Ataxia with 4x therapy for 3 weeks is effective in improving movement control, eliciting reflexes, increasing core stability and lower extremity muscle strength, and increasing functional activity.